Long-term results of the AIEOP MH'96 childhood Hodgkin's lymphoma trial and focus on significance of response to chemotherapy and its implication in low risk patients to avoid radiotherapy. Issue 11 (2nd November 2018) - Burnelli, Roberta; Rinieri, Simona; Rondelli, Roberto; Todesco, Alessandra; Bianchi, Maurizio; Garaventa, Alberto; Zecca, Marco; Indolfi, Paolo; Conter, Valentino; Santoro, Nicola; Aricò, Maurizio; Cesaro, Simone; et al.
Abstract: Identify a subset of early-stage HL children (GR1) curable with limited chemotherapy+/-radiotherapy; improve outcome of intermediate (GR2) and high-risk (GR3) patients; establish impact of response to chemotherapy evaluated with conventional imaging (CI). One hundred and sixty GR1-patients received 3ABVD + involved-field (IF) low-dose (LD) (20 Gy) irradiation if mediastinal mass or partial response (PR) after chemotherapy. Eighty-five GR2- and 315 GR3-patients received 4 and 6 COPP/ABV + IFRT, respectively. The 63 GR1 patients spared from radiotherapy had 15-year survival and EFS of 100 and 84.5%, respectively. The GR2 and GR3 15-year FFP were 84.7 and 78.6%, respectively. No different prognosis for patients in CR or PR evaluated during and after chemotherapy was observed. In conclusion, low-risk patients in CR may be successfully treated with radiation-free, low-intensity chemotherapy. Good, but less satisfactory, results were registered in GR2 and GR3. Response evaluated with CI is not a prognostic factor, but permits identification of low-risk patients who can avoid radiotherapy.